Density Functional Theory Study on Metal-Binding Energies for Human Serum Transferrin-Metal Complexes. (14th March 2012) - Sakajiri, Tetsuya; Yajima, Hirofumi; Yamamura, Takaki
Abstract : The absolute values of the metal-binding energies of human serum transferrin (Tf) N-lobe, | Δ E |, were calculated using the density functional theory and were found to increase in magnitude in the following order: Fe(III)>Ga(III)>Al(III)>Cu(II)>Zn(II)>Ni(II). The calculated energies were well correlated with the logarithmic values of the reported metal-binding constants of Tf, which had been experimentally determined, with a correlation coefficient of 0.96. In the estimation of the binding energies, the solvation energies (solvent effect) of free metal ions were a very important factor. The results provide a theoretical explanation for the binding of Fe(III) to Tf, which produces sufficient energy to induce a conformational transition of the Tf molecule, making it possible to interact with Tf receptor 1.